Pemberdayaan Perempuan Nelayan melalui Pelatihan Pengolahan Hasil Ikan menjadi Krupuk Bernilai Ekonomis di Desa Gisikcemandi Kecamatan Sedati Kabupaten Sidoarjo - Yuniningsih; Dwi Suhartini (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
The purpose of this research was to foster the entrepreneurial spirit of housewives from the fishermen’s wife in Gisik Cemandi Village. This was intended to increase family income by innovating, creativity in utilizing local wisdom owned by the village. The methods used in this community development were counseling, training, and mentoring. The training involved 30 housewives and housewives were divided into 6 groups. After counseling and training on another day, it was useful to evaluate the results of previous counseling and training. The results of this counseling and training were participants getting the knowledge, skills in making fish crackers. In addition, there was awareness of the trainee in entrepreneurship by utilizing marine products to increase income that impact on improving family welfare. The value of this dedication could be developed into a home industry if done intensive assistance with various ABDIMAS programs.